Analysis of The Effectiveness of Home-School Cooperation in Preventing Bullying in Meihekou Yuxiu Primary School - peng, Wang zhao; Soriano, Dahlia (EDUTREND: Journal of Emerging Issues and Trends in Education, 2026)
School bullying remains a pervasive issue, significantly impacting students' physical and mental well-being. This study examines the effectiveness of home-school cooperation in preventing bullying at Meihekou Yuxiu Primary School. Utilizing a qualitative research approach, semi-structured interviews were conducted with parents, teachers, and school administrators to assess current cooperation models, identify challenges, and explore strategies for improvement. The findings reveal that while home-school collaboration plays a crucial role in mitigating bullying incidents, gaps persist in communication, parental engagement, and school-led interventions. Results indicate that enhancing teacher training, establishing systematic family-school communication mechanisms, and fostering parental participation can significantly improve bullying prevention efforts. Additionally, the study emphasizes the necessity of psychological support for students and the implementation of targeted intervention programs. The conclusions provide valuable insights for optimizing home-school cooperation strategies and strengthening anti-bullying measures in primary education.